Towards Equal? Women in Central America - World Bank Group (World Bank, Washington, DC, 2018)
Central America lags the rest of Latin America in outcomes related to women. The countries of Central America (Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, and Panama) have taken important steps toward increasing the inclusion of women and improving their social and economic outcomes. This report takes stock of this progress as well as continuing challenges faced by women in the region. It assesses women's legal rights and protections, access to endowments and economic opportunities, and manifestations of agency. A crucial message of this report is that the persistence of gender norms that limit women's roles and voices remains a key obstacle to increasing economic and social inclusion.